2021
DOI: 10.1108/apjml-12-2020-0846
|View full text |Cite
|
Sign up to set email alerts
|

Examining the consequences of adaptive selling behavior by door-to-door salespeople in the Korean cosmetic industry

Abstract: PurposeThis paper aims to assess the effect of adaptive selling behavior on customer outcomes, mutual outcomes and salesperson outcomes.Design/methodology/approachThe respondents were salespeople and customers in selected door-to-door cosmetics companies in South Korea. A questionnaire was used to collect the data. Structural equation modeling was used to analyze the data in this study.FindingsFindings show that adaptive selling behavior positively affects customer satisfaction, customer loyalty, sales perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…The study also discovers that adaptive selling behaviour has a significant positive effect on sales performance. This finding backs up previous findings (Amenuvor et al. , 2021b) that adopting an adaptive selling orientation improve sales performance by allowing salespeople to better serve customers by adapting the selling approach to the specific type of customer or selling situation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The study also discovers that adaptive selling behaviour has a significant positive effect on sales performance. This finding backs up previous findings (Amenuvor et al. , 2021b) that adopting an adaptive selling orientation improve sales performance by allowing salespeople to better serve customers by adapting the selling approach to the specific type of customer or selling situation.…”
Section: Discussionsupporting
confidence: 88%
“…The study also discovers that adaptive selling behaviour has a significant positive effect on sales performance. This finding backs up previous findings (Amenuvor et al, 2021b) that adopting an adaptive selling orientation improve sales performance by allowing salespeople to better serve customers by adapting the selling approach to the specific type of customer or selling situation. As a result, while there appears to be some confusion about the actual effect of adaptive selling behaviour on sales performance, with some scholars arguing for nonsignificant relationships, our study lends credence to previous studies that found a positive relationship and cements the fact that adaptive selling (though context-specific) improves sales performance.…”
Section: Summary Of Findingssupporting
confidence: 87%
See 1 more Smart Citation
“…Second, based on long-term and friendly relationships, door-to-door salespeople often recommend customers total care solutions, along with cross-selling of skin care and makeup products (Yi et al , 2021). Third, previous studies have chosen door-to-door salespeople as a sample for studying CSB (Polonsky et al , 2000; Vieira, 2022) and sales behavior (Amenuvor et al , 2022a, 2022b; Yi et al , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Customer-oriented salespeople are interested in learning how to understand consumers by paying attention to their needs and then providing the best solutions to those problems, rather than simply making sales. Short-term gain sales-oriented salespeople, on the other hand, seek to maximize their profits as soon as possible [11,30,31]. Understanding these two concepts, however, is vital for understanding that a high level of customer orientation does not always imply a low level of sales orientation.…”
Section: Sales-oriented and Customer-oriented (Soco) Behaviorsmentioning
confidence: 99%